Episodes as Memory Units in Discourse Representation: Anaphor Use in English and Mandarin - Pu, Ming-Ming; Prideaux, Gary D.; Stanford, Lois M. (Linguistica Atlantica, 1992)
The present study investigates the relationship between cognitive constraints and discourse processing. In particular, it examines how the hierarchical structure of discourse is organized and presented, and what consequences that structure has for the linguistic coding employed during the dynamic time course of discourse processing. Special attention is directed to the distribution of full NPs and pronouns in discourse as a function of the location of episode boundaries. Results obtained from an experiment support the hypothesis that episode structure governs the alternative use of anaphora.